2015
DOI: 10.1016/j.neuropsychologia.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Learning temporal statistics for sensory predictions in mild cognitive impairment

Abstract: Training is known to improve performance in a variety of perceptual and cognitive skills. However, there is accumulating evidence that mere exposure (i.e. without supervised training) to regularities (i.e. patterns that co-occur in the environment) facilitates our ability to learn contingencies that allow us to interpret the current scene and make predictions about future events. Recent neuroimaging studies have implicated fronto-striatal and medial temporal lobe brain regions in the learning of spatial and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…The cognitive and fMRI data used in this study were collected in the context of two behavioral and fMRI studies (Baker et al, 2015; Luft et al, 2015, 2016) in which the participants were asked to predict the orientation of a test stimulus following exposure to structured sequence of leftwards and rightwards oriented gratings, and no feedback were given. Both studies aimed to (1) test whether training on structured temporal sequences improves the ability to predict upcoming sensory events and (2) identify brain regions that support the ability of using implicit knowledge about the past for predicting future.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cognitive and fMRI data used in this study were collected in the context of two behavioral and fMRI studies (Baker et al, 2015; Luft et al, 2015, 2016) in which the participants were asked to predict the orientation of a test stimulus following exposure to structured sequence of leftwards and rightwards oriented gratings, and no feedback were given. Both studies aimed to (1) test whether training on structured temporal sequences improves the ability to predict upcoming sensory events and (2) identify brain regions that support the ability of using implicit knowledge about the past for predicting future.…”
Section: Methodsmentioning
confidence: 99%
“…In Luft et al (2016), regions-of-interest (ROIs) were identified by applying whole-brain general linear model analysis with a voxel-wise mixed-design three-way ANOVA, that is,…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations